Diffie-Hellman Key Exchange through Steganographied Images - Khaldi, Amine (Law, State and Telecommunications Review, 2018)
Purpose ”“ In a private key system, the major problem is the exchange of the key between the two parties. Diffie and Hellman have set up a way to share the key. However, this technique is not protected against a man-in-the-middle attack as the settings are not authenticated. The Diffie-Hellman key exchange requires the use of digital signature or creating a secure channel for data exchanging to avoid the man-in-the-middle attack. Methodology/approach/design ”“ We present a Diffie-Hellman key exchange implementation using steganographied images. Using steganography made invisible the data exchange to a potential attacker. So, we will not need a digital signature or creating a secure channel to do our key exchange since only the two concerned parts are aware of this exchange. Findings ”“ We generate a symmetric 128-bit key between two users without use of digital signature or secure channel. However, it works only on bitmap images, heavy images and sensitive to compression.